An evaluation of the school feeding programme as a service delivery mechanism to improve academic performance of needy learners in Bonteheuwel - Swartz, Andrew Mervyn (Cape Peninsula University of Technology, 2009)
The study centres on the school feeding programme in the Bonteheuwel area, which is a predominantly Coloured residential area in close proximity to Cape Town International Airport. The school feeding programme is a national initiative that is driven by the Western Cape Education Department on a provincial level. The research investigated whether the school feeding scheme is being implemented effectively and efficiently. This implies that it was necessary to determine:  The current status of school feeding in Bonteheuwel;  Whether it adequately meets the needs of needy learners; and  If the current scheme is found to be inadequate, what can be done to improve the situation? As the study uses both descriptive and empirical approaches, a questionnaire was constructed to obtain views of selected members of Bonteheuwel’s community. Responses to the questions/statements in the questionnaire were analysed by a Cape Peninsula University of Technology registered statistician and the statistical analysis provided positive answers to the above determinations, which revealed that the school feeding programme was not effective and that more should be done to improve its delivery. The final chapter proposes a number of recommendations to improve implementation of the school feeding programmme.
Thesis (MTech (Public Management))--Cape Peninsula University of Technology, 2009
Keywords: School children -- Food -- Bonteheuwel (South Africa); School children -- Nutrition -- Bonteheuwel (South Africa); Food relief -- Bonteheuwel (South Africa)